Mozambique: Joint sector review assessment: Advancing mutual accountability through comprehensive, inclusive, and technically robust review and dialogue - Ministry of Agriculture, Mozambique (Government of Mozambique, Ministry of Agriculture, 2014)
This report is part of the overall approach to agricultural development in Mozambique set in motion by the National Agricultural Investment Plan (NAIP) (referred to in Mozambique as the Plano Nacional de Investimento do Sector Agrário, or PNISA). This process takes place within the context of the mutual accountability framework of the Comprehensive Africa Agriculture Development Plan (CAADP). This report is a preliminary step to successfully establish within the country the process of the joint sector review (JSR). The JSR is a mutually accountable dialogue platform to review progress toward agreed-upon goals, assess implementation of stakeholders’ commitments, and help set agricultural sector policy and priorities. The aim of this report is to inform stakeholders of progress in PNISA’s implementation. PNISA was enacted to achieve the objectives set in the framework of CAADP and the Strategic Plan for Agricultural Development 2011–2020 (Plano Estratégico de Desenvolvimento do Sector Agrário, or PEDSA).